The Necessity of the Discipline of Pure Reason for the Systematicity of the Practical Use of Reason in Kant’s Critical Philosophy - Baghai, Farshid (Con-Textos Kantianos. International Journal of Philosophy, 2023)
Kant’s critical philosophy cannot realize its stated purpose to make metaphysics systematic unless it makes all metaphysical uses of reason, including the practical use of reason, systematic. Yet Kant’s account of the systematicity of the practical use of reason is not entirely clear. In particular, none of the variations of his account of the systematicity of the practical use of reason explicitly discusses the role of the discipline of pure reason in making the practical use of reason systematic. The apparent absence of the discipline from Kant’s account is contrary to indications in his writings indirectly suggesting that the discipline plays an indispensable role in the systematicity of the practical use of reason. This discrepancy remains unaddressed in the scholarship. Most interpreters reconstruct Kant’s account of the systematicity of the practical use of reason without attributing any role to the discipline. This article aims to make explicit the role of the discipline in Kant’s account of the systematicity of the practical use of reason. Specifically, it suggests that the discipline of pure reason is the first necessary condition for the systematicity of the practical use of reason: it prepares the ground for a justifiable conception of the ideal of the highest good and for legitimate postulates regarding the immortality of the soul and the existence of God.